Looking Beyond the Bridge: How Temporary Agency Employment Affect Labor Market Outcomes - Elke J. Jahn; Michael Rosholm (Verein für Socialpolitik, 2010)
This paper comprehensively analyzes the stepping-stone effect of temporary agency employment. Using the timing-of-events approach, we not only investigate whether temporary agency employment is a bridge into regular employment but also at the individual's post-unemployment wages and post-unemployment job stability for Danish unemployed workers. We find evidence for large positive treatment effects. Agency employment is particularly a successful search strategy for immigrants. Moreover, our results suggest that taking up a temp job may improve the quality of post-unemployment jobs in terms of employment stability and post-wages indicating that agency employment may improve subsequent matching quality.
Keywords: C41; J64; J40; 330; temporary agency employment; stepping stone; employment stability; earnings; Denmark